The impact of dog phobia severity on views regarding stray dog management in Türkiye - Demir Pervane, Vasfiye; Uyar, Betül; Erten Bucaktepe, Pakize Gamze (Frontiers in Veterinary Science, 2025)
Background and objectivesThe aim of this study was to evaluate the opinions of individuals regarding the management of stray dogs and its relationship with dog phobia.Materials and methodsThe study was a cross-sectional analytical study, and data were collected online across Türkiye. Of 1,359 participants, 63.1% of the participants were female and 89.6% were university graduates. 69.5% of participants had any level of dog phobia. Younger individuals, those without pets or experience with stray animals, and those with a history of dog attacks showed higher phobia rates (all p < 0.001). Fear of stray dogs, being attacked, and contracting rabies were common concerns, correlating with higher phobia levels (p < 0.001). The rates of supporting vaccinating and neutering dogs were 92.3 and 49.8%, respectively. Of the respondents, 53.3% agreed with keeping neutered dogs in shelters. It has been found that people who do not own dogs [OR: 1.779 (95% CI: 1.005–3.150), p = 0.048] and cats [OR: 1.931 (95% CI: 1.044–3.572), p = 0.036]; who had never provided care for stray animals [OR: 2.034 (95% CI: 1.467–2.821) p < 0.001] and those with a personal or family history of having been attacked by a dog than in those [OR: 2.101 (95% CI: 1.631–2.706) p < 0.001] are approximately twice as likely to have a phobia. Participants with dog phobia were 65.5% less likely to agree that dogs that have been vaccinated and neutered should be left on the streets again [OR: 0.345 (95% CI: 0.270–0.441) p < 0.001], and those with dog phobia were 2.6 times more likely to state that dogs that have been vaccinated and neutered should be kept in shelters and given the necessary care [OR: 2.649 (95% CI: 2.078–3.377) p < 0.001].ConclusionDog phobia is prevalent, and stray dog management significantly influences public fear levels and perceptions. Understanding the relationship between dog phobia and attitudes toward stray dog management can help inform policies that address both public concerns and animal welfare. More representative studies are needed to better reflect the general population.